Perlindungan Hukum Pihak Ketiga dalam Hak atas Tanah di Atas Tanah Negara yang Berubah Status - Widyanti, Amelia Nur (Postgraduate of Jayabaya University, 2023)
Indonesia's ongoing development necessitates the existence of the right of management, which delegates state control over land use for the achievement of public welfare. In spite of ongoing controversies, it remains an important part of Indonesian development. The lack of recognition of its importance may be the cause of unresolved land issues. Given the very heterogeneous nature of Indonesian society and the diverse land structures, the right of management is a necessary reality. Such an analysis shall take into consideration legal protection of holders of construction rights on government lands which are converted into construction rights under management rights, as well as legal protection of holders of construction rights on government lands which are converted into construction rights under management rights. It is crucial to examine the ownership rights of land for the holders of construction rights under management rights. This examination is based on the principle of justice in connection with the right of state control in the development of land law in Indonesia.